Bad animals, techno-fixes, and the environmental narratives of alternative protein - Hedberg, Russell C. (Frontiers in Sustainable Food Systems, 2023)
In the last decade animal agriculture has received significant scrutiny for its many negative environmental consequences. In response to these myriad concerns a wide range of voices have advocated for diets that include less animal products (meat, dairy, eggs), often arguing that animal-based diets are inherently more resource intensive than those based on plants. Prominent in this discourse is a narratives formation developed by a slew of venture capital-backed food technology startups known as alternative protein that I refer to as the bad animal narrative. This narrative argues that livestock are fundamentally bad technology, and the solution to the many environmental problems of animal agriculture is to replace livestock with novel technologies to produce animal product alternatives that will satisfy consumer demand while also solving one of the fundamental environmental challenges of modern agriculture. In this paper I use discourse analysis frameworks from political ecology and science and technology studies to examine a large corpus of publicly available text that includes alternative protein company websites, mission statements, blogs, and connected media pieces, as well as life cycle assessment reports documenting the environmental impacts of alternative protein products as well as conventionally and alternatively produced livestock. This analysis finds that the bad animal narrative places blame on livestock without clearly providing evidence, and it rests on a set of problematic assumptions about the current food system and its possible futures. Analysis of life cycle assessment statistics finds that the industrial system, rather than livestock themselves, is the chief driver of the environmental problems of animal agriculture. The paper concludes with a consideration of the future food system envisioned by the bad animal narrative and its implications for sustainability.